A study of users’ perception towards road maintenance on the Kota Kinabalu-Keningau Federal Road / Nurhanana Nadzihah ... [et al.] - Nadzihah, Nurhanana; Abdul Rashid, Robiah; Zahari, Nurul Fadzila; Wan Ismail, Wan Zuriea; Kamarudin, Hikmah (2023)
Roads play a crucial role in a nation's transportation network and are vital for economic development. Efficient and well-maintained roads facilitate the smooth flow of people and goods, contributing to the nation's economy. However, despite annual budget allocations for road maintenance and agreements between the government and concession companies responsible for maintenance, poor road conditions still persist. This research aims to understand the importance of road maintenance, evaluate user satisfaction levels with maintenance efforts, and propose strategies to address road maintenance issues on the Kota Kinabalu-Keningau federal road. The findings revealed that road users were dissatisfied with the implemented road maintenance, while their assessment of the road conditions was neutral. However, certain aspects related to road conditions, such as safety, road surface condition, and road furniture and amenities, received poor ratings. To address these issues, several strategies were recommended on federal road and incorporating site observations as an additional method for the study.